Systematic Literature Review: Penerimaan Game-Based Learning Dalam Pendidikan Menggunakan TAM - Septiono Raka Wahyu Sasongko; Arista Pratama; Asif Faroqi (MDP Student Conference, 2026)
This study aims to analyze the application of the Technology Acceptance Model (TAM) in the context of game-based learning technologies using a Systematic Literature Review (SLR) approach. The SLR process involved several stages, including the formulation of research questions, article searching, article selection based on inclusion and exclusion criteria, and quality assessment. A total of 18 articles were identified and analyzed to examine the implementation of TAM, the external variables incorporated, and the relationships among variables within the model.The findings indicate that perceived ease of use and perceived usefulness consistently serve as the core internal variables influencing the intention to use game-based learning technologies. Furthermore, most studies employed modified versions of TAM by integrating external variables aligned with the characteristics of educational games, such as enjoyment, social influence, self-efficacy, and motivation. The relationships among variables demonstrate consistency with TAM’s fundamental constructs, particularly perceived ease of use and perceived usefulness. These results confirm that TAM is an appropriate and relevant model for analyzing the acceptance of game-based learning technologies in the field of education.